Prevalence of autism traits and attention-deficit hyperactivity disorder symptoms in a clinical sample of children and adolescents with chronic pain - Lipsker, C.; Bölte, Sven; Hirvikoski, T.; Lekander, M.; Holmström, L.; Wicksell, R. (2018)
Purpose: Recent research has suggested that autism spectrum disorder (ASD) and attention-deficit hyperactivity disorder (ADHD) may be comorbid to pediatric chronic pain, but the empirical support is yet scarce. Therefore, the current study aimed to investigate the occurrence of traits and symptoms consistent with clinically significant ASD and ADHD in a group of children and adolescents with chronic debilitating pain and examine potential differences in pain and demographic variables between children with and without clinically significant traits and symptoms of ASD and ADHD. Patients and methods: This cross-sectional study included 146 parent–child dyads (102 girls, 111 mothers, children 8–17 years) consecutively referred to a tertiary pain clinic. Parents completed the Social Responsiveness Scale to assess autistic traits, and Conners-3 to measure symptoms of ADHD in their children. Children completed the Lübeck Pain Questionnaire to evaluate experienced pain. Results: Among children, 20 (13.7%) received scores consistent with clinically significant ASD and 29 (19.9%) received scores consistent with clinically significant ADHD, with a combined prevalence of clinically significant ASD/ADHD traits and symptoms of 26% of the total sample. Only 4.8% of children were previously diagnosed with either disorder. Among children with clinically significant ASD traits, girls were more prevalent, parents reported lower health, and the pain was more likely triggered by being in school. Among children with clinically significant ADHD symptoms, there were no gender differences and pain was more likely triggered by the family situation and new situations. No differences regarding pain intensity, duration, or frequency were found between children with and without clinically significant ASD traits or ADHD symptoms. Conclusion: Children with debilitating chronic pain, particularly girls, may present with an elevated risk of having a comorbid, possibly high-functioning, neurodevelopmental disorder. Results suggest that clinical assessment of pediatric chronic pain should include screening for neurodevelopmental disorders.